Development of a live attenuated vaccine candidate for equid alphaherpesvirus 1 control: a step towards efficient protection - Hu, Yue; Wu, Guiling; Jia, Qinrui; Zhang, Baozhong; Sun, Wencheng; Sa, Ruixue; Zhang, Siyu; Cai, Weifan; Jarhen,; Ran, Duoliang; Liu, Jianhua (Frontiers in Immunology, 2024)
Equid alphaherpesvirus 1 (EqAHV1) is a viral pathogen known to cause respiratory disease, neurologic syndromes, and abortion storms in horses. Currently, there are no vaccines that provide complete protection against EqAHV1. Marker vaccines and the differentiation of infected and vaccinated animals (DIVA) strategy are effective for preventing and controlling outbreaks but have not been used for the prevention of EqAHV1 infection. Glycoprotein 2 (gp2), located on the envelope of viruses (EqAHV1), exhibits high antigenicity and functions as a molecular marker for DIVA. In this study, a series of EqAHV1 mutants with deletion of gp2 along with other virulence genes (TK, UL24/TK, gI/gE) were engineered. The mutant viruses were studied in vitro and then in an in vivo experiment using Golden Syrian hamsters to assess the extent of viral attenuation and the immune response elicited by the mutant viruses in comparison to the wild-type (WT) virus. Compared with the WT strain, the YM2019 ∆gp2, ∆TK/gp2, and ∆UL24/TK/gp2 strains exhibited reduced growth in RK-13 cells, while the ∆gI/gE/gp2 strain exhibited significantly impaired proliferation. The YM2019 ∆gp2 strain induced clinical signs and mortality in hamsters. In contrast, the YM2019 ∆TK/gp2 and ∆UL24/TK/gp2 variants displayed diminished pathogenicity, causing no observable clinical signs or fatalities. Immunization with nasal vaccines containing YM2019 ∆TK/gp2 and ∆UL24/TK/gp2 elicited a robust immune response in hamsters. In particular, compared with the vaccine containing the ∆TK/gp2 strain, the vaccine containing the ∆UL24/TK/gp2 strain demonstrated enhanced immune protection upon challenge with the WT virus. Furthermore, an ELISA for gp2 was established and refined to accurately differentiate between infected and vaccinated animals. These results confirm that the ∆UL24/TK/gp2 strain is a safe and effective live attenuated vaccine candidate for controlling EqAHV1 infection.